Treatment of vesicouretheral reflux in pediatric patients - Grebeldinger Slobodan; Radojčić Branka; Meljnikov Igor; Balj Svetlana (Vojnosanitetski Pregled)
Background/Aim. Vesicouretheral reflux (VUR) is an inherited abnormality of the urinary tract caused by dysfunction of vesicouretheral junction frequently accompanied by recurrent urinary infection. The optimal treatment method of VUR is still controversial. The aim of the study was to analyze medical charts of children with VUR with special focus on the results of endoscopic treatment with Deflux. Methods. This retrospective study analyzed the medical charts of all children diagnosed with VUR at the Institute for Children and Youth Health Care of Vojvodina, in five years period. The analyzed data were: age, gender, grade, bilateral or unilateral presence of reflux, distribution to the sides of the body, urinary tract infections, associated anomalies and complications of VUR, treatment methods and the success rate of endoscopic correction with Deflux. Data processing was performed using the standard statistical methods. Results. The study included 167 patients (101 females and 66 males) with 231 refluxing ureters. The patients age at diagnosis was 1 month to 18 years (mean 4.6 years). Frequencies of different grades of VUR at initial investigation were: 17%, 27%, 22%, 21% and 13% for grades I to V, respectively. VUR was unilateral in 103 patients (left in 65 and right in 38), and bilateral in 64. Urinary tract infections were present in 78.4% of patients, reflux nephropathy in 38.3%, hypertension in 3.0%, chronic renal insufficiency in 4.8%, associated anomalies in 39.5% of patients. The treatment method was recorded in 154 cases. Medically were treated 80 patients, and surgically 74. Endoscopic injection of Deflux was carried out in 59 patients. From 79 ureters treated, five had grade I reflux, 11 grade II, 23 grade III, 27 grade IV, and 13 grade V. In 46 patients Deflux injection was carried out once. A second injection was required in eight, and third injection in five patients. Reflux was absent in 42 of the treated patients (71.2%) and 15 patients (25.4%) had a decreased grade of reflux after the treatment. Overall success rate was 96.6%. Conclusion. Endoscopic subureteral injection of Deflux is a minimally invasive method for VUR treatment in pediatric patients.